Political Correctness : a Response from the Cultural Left. - Feldstein, Richard (University of Minnesota Press, 1997)
Written with refreshing clarity and wit, Political Correctness describes a cultural nonphenomenon brought into being by the desires of neoconservatives. Nostalgic for the simple moral logic of the Cold War, the conservative Right has created an evil empire within and conferred upon its enemiesfrom multiculturalists to postmodernists and poststructuralistsa McCarthyite agenda that demands action from the high-minded.